Ventricular fibrillation and Takotsubo cardiomyopathy triggered by media panic on COVID‐19: A case report. Issue 1 (3rd December 2020) - Habedank, Dirk; Thieme, Roland; Bublak, Angelika; Heinemann, Felix; Spencker, Sebastian; Atmowihardjo, Iskandar
Abstract: Takotsubo cardiomyopathy has potentially lethal complications and can be caused by a media‐induced diffuse atmosphere of life threatening and panic in preconditioned patients. Abstract : Takotsubo cardiomyopathy has potentially lethal complications and can be caused by a media‐induced diffuse atmosphere of life threatening and panic in preconditioned patients.